MENGUPAYAKAN ANTUSIASME DALAM PEMBERDAYAAN KARUNIA BERBAHASA ROH - Saputra, rudyanto Chandra (Shift Key : Jurnal Teologi dan Pelayanan, 2023)
Enthusiasm is energy that vibrates at the highest level, energy that vibrates in harmony with creation. When one feels enthusiastic one is on a journey of divinity. The gift of tongues is a special ability given by God to some members of the Body of Christ to speak to God in an unlearned language and to receive and deliver a message directly from God to His people. This research aims to describe how the enthusiasm of the congregation can be built in the implementation of the empowerment of the gift of tongues. The research method used is a literature study. The results of library searches and research results show that enthusiasm is built with motives, passion, models and impartation.